Eco-landscape - Jeong, Ji-seong. ([Seoul, Korea] : CA Press, 2006)
Sky Landscape explores the variety of high-rise buildings and the technologies behind them that make them not only effective as the buildings themselves, but also harness the natural environmental factors that make them more ecology and energy efficient
"Ecological landscape"--Back cover.
Text in English and Korean.
Keywords: Ecological landscape design -- Korea; Landscape design -- Korea